Prevalence and risk of bone fractures in patients with chronic pancreatitis: meta-analysis - D. N. Andreev; I. V. Maev; Yu. A. Kucheryavyy (Научно-практическая ревматология, 2021)
Aim: to systematize data on the frequency and risk of bone fractures in patients with chronic pancreatitis.Methods. MEDLINE/PubMed, EMBASE, Cochrane, Google Scholar through October 2020 were searched to identify studies evaluating the prevalence of bone fractures in chronic pancreatitis. For the final analysis, publications with detailed descriptive statistics (total sample size, number of patients with chronic pancreatitis, number of control persons, number of patients with fractures in groups) were selected, allowing the resulting data to be included in the meta-analysis.Results. The final analysis included 6 studies involving 2 025 918 people (18 844 patients with chronic pancreatitis; 2 007 074 – control subjects). The generalized incidence of fractures in patients with chronic pancreatitis was 14.09% (95% CI: 5.877–25.098). There was significant heterogeneity between the results (p<0.0001; I2=99.58%). Chronic pancreatitis significantly increases the risk of fractures in comparison with control subjects with OR 2.819 (95% CI: 1.855–4.282; I2=97.14%). With the exclusion from the analysis of 2 studies with a wide 95% CI (less than 150 patients with chronic pancreatitis in each), the pooled fracture frequency was 9.25% (95% CI: 1.930–21.221; I2=99.74%).Conclusion. This meta-analysis demonstrated that CP is a risk factor for fractures. Considering this association, it is advisable to include densitometry in the routine examination algorithms for patients with chronic pancreatitis, as well as to correct osteoporosis in this category of patients in time.